CATALASE 1 GENE EXPRESSION (CAT-1) IN HYPERGLICEMIA INDUCED TESTIS, AS AN ANTIOXIDANT THERAPY INDICATORS - Zulfan, Ahmad; Wonatorey, Nickanor K. R (Indonesian Urological Association, 2021)
Objective: This study aims to analyze the effects of hyperglycemia status on the function of testicular spermatology, especially CAT-1. Material & Methods: This study was an experimental pre-clinical study. Twenty-seven rats were divided into 3 groups: normal, 2 weeks, and 4 weeks hyperglycemia. The hyperglycemic state in the Wistar rats was induced by Streptozotocin (STZ). All data were collected and analyzed with SPSS 20.0. At two and four weeks, testicular tissue was extracted and it will be processed using the Total RNA Mini Kit FavorPrepTM then quantitative PCR was performed using the SYBR® Fast qPCR Kit. Results: CAT-1 gene expression in the hyperglycemia induction group increased when induced for 2 weeks and again after 4 weeks compared to controls (18.88 ± 4.7 and 21.45 ± 5.52 vs 10.83 ± 3.4). However only induction after 2 weeks was statistically significant (p= 0.021). Conclusion: CAT-1 (Catalase) gene expression has increased in testicular tissue under conditions of hyperglycemia.